Fatigue behaviour of macrofiber reinforced gap graded asphalt mixtures - Morea, Francisco (2020)
The addition of fibres to reinforce asphalt mixtures is a prospective field for pavement engineering, where the use of glass or synthetic macrofibers could potentially help not only as reinforcement for new asphalt mixtures, but also as part of asphalt overlays applied on deteriorated pavements to diminish reflective cracking during maintenance operations. In recent studies, it has been found that the addition of macrofibres can improve the rutting and fracture resistance of asphalt mixtures. However, the response of these mixtures to fatigue has not been studied yet. In this study, a complete performance characterization of a gap graded asphalt mixture with the addition of glass and synthetic macrofibres was studied. Also, a reference asphalt mixture without macrofibres was provided for comparison. Results showed that the addition of macrofibres improves water sensibility, rutting performance and stiffness of the gap grade asphalt mixtures studied. Also, it was observed during the fatigue tests that the incorporation of both types of macrofibres greatly improved the durability of the mixtures to fatigue cracking at medium range temperatures. This improved fatigue behaviour correlates to an extended useful life for the fibre reinforced asphalt mixtures. The synthetic macrofibres showed better fatigue behaviour at lower temperatures, while glass macrofibres gave a better response at the higher temperature studied.